Information and communication technology skills and editorial competence as factors influencing quality textbook production by publishers in South-West, Nigeria (2019)
Textbooks occupy a pride of place in book publishing business and adoption of Information and Communication Technology (ICT) skills has empowered editors to attain proficiency and competence. This study examined ICT skills and editorial competence as factors influencing quality educational textbooks production by publishers in South-west, Nigeria. Survey method was adopted for the study, questionnaire was the research instrument, while four research questions were formulated. Population was the 62 publishing firms in South-west Nigeria while sample for the study was the publishing staff of twelve randomly selected publishing companies. Data was analysed using percentages and statistical mean. Findings showed that ICT skills and editorial competence were crucial factors that influenced the quality of educational textbooks in South-west, Nigeria. The study recommended that ICT skills acquisition and editorial empowerment should be emphasised by publishers to achieve quality educational textbooks.